Work-Life Balance and Professional Burnout: Evidence from Law Enforcement in Southern Cebu - Berou Jr., Aniceto; Calang, Veronica; Villahermosa, Mardy; Israel, Edelbert; Li Alfante, Adrian; Evalle, Margie; Kelsey Saplad, Rey; Pardillo, Bernardo (The American Journal of Interdisciplinary Innovations and Research, 2026)
Law enforcement officers, particularly patrolmen, face chronic occupational stressors that disrupt work-life balance and contribute to burnout—a syndrome marked by emotional exhaustion, depersonalization, and diminished personal accomplishment. This study examined the correlation between work-life balance and burnout among patrolmen (n=18) in the City of Naga and San Fernando, Southern Cebu, Philippines. A quantitative-correlational design was employed using a validated survey grounded in the Maslach Burnout Inventory (MBI) and Spearman’s rank correlation. Most respondents (94.4%) rarely disconnect from work outside working hours. Emotional exhaustion registered a moderate weighted mean of 3.08. Depersonalization showed zero variance, precluding correlation analysis. Work-life balance showed no significant correlation with emotional exhaustion (ρ = -0.219, p = 0.383) or personal accomplishment (ρ = -0.157, p = 0.533). Findings reveal notable emotional exhaustion and work-life imbalance. Organizations should implement workload redistribution, stress management, and wellness-supportive policies to protect officer well-being.